Impact of rapid thermal annealing on Mg‐implanted GaN with a SiOx/AlN cap‐layer. Issue 4 (23rd November 2016) - Khalfaoui, Wahid; Oheix, Thomas; El‐Zammar, Georgio; Benoit, Roland; Cayrel, Frederic; Faulques, Eric; Massuyeau, Florian; Yvon, Arnaud; Collard, Emmanuel; Alquier, Daniel
Abstract : Local p‐type doping in GaN is a key issue for device development but it remains a challenge to be achieved. In this work, we studied the activation of Mg implanted in the GaN. Multi‐energy implantations were performed to achieve a "box‐like" profile. SIMS measurements showed unexpected deep Mg profile due to defect‐assisted channeling in the GaN. In addition, a high‐density defect region induced by the implantation was evidenced by TEM characterization. To protect the GaN surface prior to high temperature annealing, an AlN cap‐layer was deposited by reactive sputtering followed by SiO x deposition leading to a double cap‐layer. Afterwards, the capped samples were RTA‐annealed at high temperatures for several minutes under nitrogen. Two types of annealing processes were applied: a monocycle and a multicycle annealing. After annealing, the double cap‐layer was etched using chemical solutions. AFM characterizations, after annealing and cap‐layer etching, demonstrated that a GaN surface with similar roughness to as‐grown samples and pit‐free can be achieved after both monocycle and multicycle annealing steps. However, an AlGaN layer at the AlN/GaN interface is observed by ToF‐SIMS and remained after the etching of the AlN layer. Finally, Schottky diodes were processed on the unimplanted and annealed samples, evidencing a double barrier, while P/N junction diodes are still being processed on the implanted and annealed samples.